Hepatosplenic fusion in a cadaver - An extremely rare variation - Ghosh, Anasuya; Amit Kumar Pal, (Asian Journal of Medical Sciences, 2023)
Anatomical variations are observed at times during routine dissection processes or conduction of autopsies or may be found incidentally during radiological investigations. Fusion of the liver and spleen is an extremely rare condition that has been mentioned only a few times in the literature. “Beaver tail liver” is a variation of the liver where the left lobe of the liver is elongated and extends across the midline toward left hypochondrium of abdomen, often touching and encircling the spleen. Some of these cases may mimic hemorrhage and trauma within and around the spleen in ultrasound imaging or computed tomography scan. In certain cases, the liver and the spleen are difficult to distinguish due to their identical sonographic and radiological properties. Prior knowledge of such instances will help to interpret and manage such cases when encountered.